2020
DOI: 10.1177/2325967120964476
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics in an Incomplete Versus Complete Supraspinatus Tear: A Cadaveric Study

Abstract: Background: Degenerative and traumatic changes to the rotator cuff can result in massive and irreparable rotator cuff tears (RCTs). Purpose/Hypothesis: The study objective was to conduct a biomechanical comparison between a small, incomplete RCT and a large, complete RCT. We hypothesized that the incomplete supraspinatus (SS) tear would lead to an incremental loss of abduction force and preserve vertical position of the humeral head, while a complete SS tear would cause superior humeral migration, decrease fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“… 12 Due to superior rotator cuff anatomy, full-thickness traumatic supraspinatus lesions are strongly associated to glenohumeral capsule lesions. 24 Fetal anatomical studies showed that, since 10th week of gestation, the fibers of the deep layer of supraspinatus tendon and superior glenohumeral capsule are intimately intertwined and cannot be separate at their insertion point on greater tuberosity. 6 So, in case of traumatic supraspinatus tear, superior glenohumeral capsule tears with supraspinatus tendon deep layer, explaining why it is so unusual to find an isolated full-thickness supraspinatus tear with intact glenohumeral capsule.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Due to superior rotator cuff anatomy, full-thickness traumatic supraspinatus lesions are strongly associated to glenohumeral capsule lesions. 24 Fetal anatomical studies showed that, since 10th week of gestation, the fibers of the deep layer of supraspinatus tendon and superior glenohumeral capsule are intimately intertwined and cannot be separate at their insertion point on greater tuberosity. 6 So, in case of traumatic supraspinatus tear, superior glenohumeral capsule tears with supraspinatus tendon deep layer, explaining why it is so unusual to find an isolated full-thickness supraspinatus tear with intact glenohumeral capsule.…”
Section: Discussionmentioning
confidence: 99%
“…The machine device was designed and weighted according to the protocol described by Mihata et al 14 , 17 and as used in other similar cadaveric studies. 6 , 21 , 22 This experimental frame allowed the glenohumeral joint to be stabilized through force applied to the insertion sites of the muscles. The tendon attachments were connected to a pulley system and attached to free-hanging weights exerting the force vectors depicted in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Christopher et al 12 used a dynamic shoulder simulator to test the maximum abduction force of the deltoid muscle during the abduction process. Danil et al 13 analyzed the stress of the shoulder joint in normal patients with rotator cuff tears during abduction through biomechanical experiments. However, due to the limitations of the experimental environment and conditions, the results of many indicators are difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…Christopher et al 12 used a dynamic shoulder simulator to test the maximum abduction force of the deltoid muscle during the abduction process. Danil et al 13 analyzed the stress of the shoulder joint in normal patients with rotator cuff tears during abduction through biomechanical experiments. However, due to the limitations of the experimental environment and conditions, the results of many indicators are difficult to predict.The finite element analysis method can simulate working conditions that are difficult to carry out in biomechanics and obtain the corresponding mechanical results; it has been widely used in research on the shoulder joints.…”
mentioning
confidence: 99%